Analisis Yuridis Peran Digital Forensik Dalam Pembuktian Tindak Pidana di Indonesia - Anggraeni, Dinda Restya; Salsabila, Marsha (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The evolution of technology has impacted all sectors of life. Although it has provided many conveniences for humans, it is undeniable that technological advancements have led to the emergence of new crimes, known as cybercrime. Therefore, digital forensics is important to collect, analyze, and present digital evidence in court. This research aims to describe the role of digital forensic science in proving criminal offenses in Indonesia. In its preparation, the author uses the normative juridical method. The research shows that digital forensics plays an important role in proving criminal offenses in Indonesia. Digital forensics is crucial for finding, collecting, and reviewing evidence so it can be used in court.